Environmental Care Behavior from Knowledge and Social Environment Factors in Pasaman Barat District - Dinda Kurnia Putri; Iwan Setiawan; Annisa Joviani Astari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to see how the influence of environmental knowledge and social environment (family environment, community environment, and school environment) on environmental care behavior. This study uses a survey method conducted in six Madrasah Aliyah Negeri Pasaman Barat Regency. The sampling technique used was random sampling, so 179 respondents of class XI IS were obtained. The measuring instrument used is a questionnaire. The data analysis technique used linear regression analysis. The results showed that there was an influence of environmental knowledge and social environment on environmental care behavior, as seen in Fhit (50,909) > Ftab (3.05) of 36.6%. In fact, the most influential factor on environmental care behavior is the influence of social environmental factors on school environment indicators, followed by family environment, and community environment. Meanwhile, environmental knowledge has the least effect. Therefore, the factors that have been identified as influencing environmental care behavior should be considered in planning the development of education for indigenous peoples to achieve environmental sustainability.